2011
DOI: 10.1186/1471-2393-11-75
|View full text |Cite
|
Sign up to set email alerts
|

Waiting for attention and care: birthing accounts of women in rural Tanzania who developed obstetric fistula as an outcome of labour

Abstract: BackgroundObstetric fistula is a physically and socially disabling obstetric complication that affects about 3,000 women in Tanzania every year. The fistula, an opening that forms between the vagina and the bladder and/or the rectum, is most frequently caused by unattended prolonged labour, often associated with delays in seeking and receiving appropriate and adequate birth care. Using the availability, accessibility, acceptability and quality of care (AAAQ) concept and the three delays model, this article pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
73
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(88 citation statements)
references
References 44 publications
10
73
1
1
Order By: Relevance
“…Mselle et al, studying women with obstetric fistulae in Tanzania, reported that decision to seek care in health facilities was reached when a complication had occurred [26]. The finding that more people are engaged when a woman is in labour, and especially when labour takes longer than normal, means that not only is the economic dimension important, but also the affection and symbolic dimensions of values of saving a life become important.…”
Section: Discussionmentioning
confidence: 99%
“…Mselle et al, studying women with obstetric fistulae in Tanzania, reported that decision to seek care in health facilities was reached when a complication had occurred [26]. The finding that more people are engaged when a woman is in labour, and especially when labour takes longer than normal, means that not only is the economic dimension important, but also the affection and symbolic dimensions of values of saving a life become important.…”
Section: Discussionmentioning
confidence: 99%
“…A study in rural Tanzania showed that even at higher-level facilities where well trained health workers were supposed to be available, women experienced delays in receiving emergency obstetric care and had poor quality of care. Consequently, women experienced severe birth injuries and stillbirths [12]. When women have a choice, they will go to health facilities where they perceive better quality of care, regardless of distance [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Published accounts have found that many women and their families fail to recognise danger signs that necessitate skilled attendance at delivery or experience delays in seeking care due to lack of transportation or funds for transport; some experience delays once they reach the facility due to lack of providers, supplies, or equipment (Bangser et al, 2010; Holme, Breen, & MacArthur, 2007; Mselle, Kohi, Mvungi, Evjen-Olsen, & Moland, 2011a; Turan, Johnson, & Polan, 2007). …”
Section: Introductionmentioning
confidence: 99%